Novel modified blister test to evaluate composites used in repairing cracked pipeline - Payman Sahbah Ahmed; Jafar Abdullah Ali; Serwan Sarbast Mohammed Talabani (Polímeros, 2023)
Abstract The traditional method of fixing cracked pipes by welding needs stopping the production. In this study, a composite material is used to repair pipelines without interrupting production, saving both time and money. Hand Layup and vacuum infusion techniques were used to prepare glass strand mat and intra-ply hybrid glass - carbon fibers composites repairs. To show the composites' strength, blister, double cantilever beam, and peel tests were conducted. A novel modified blister test was utilized to show effectiveness of laboratory tests on real pipeline. The results indicate that vacuum infused intra-ply hybrid composite exhibited the highest strength. The experimental results of the best composite were compared with the finite element model under blister test, and the results were found to be identical. The modified blister test on the real pipe provides a better indication about the good strength of the composite repair compared to previous researches.